2022
DOI: 10.1186/s12934-022-01858-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum 25-hydroxyvitamin D (25(OH)D) levels with the gut microbiota and metabolites in postmenopausal women in China

Abstract: Background Vitamin D insufficiency or deficiency is associated with an altered microbiota in older men. However, the relationship between the gut microbiota and 25-hydroxyvitamin D (25(OH)D) levels remains unknown in postmenopausal women. In this study, fecal microbiota profiles for 88 postmenopausal women in the high 25(OH)D (HVD) group (n = 44) and the low 25(OH)D (LVD) group (n = 44) were determined. An integrated 16S rRNA gene sequencing and liquid chromatography–mass spectrometry (LC–MS)-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The human body contains approximately 1 to 2 kg of microorganisms per adult individual, which has been found to play a crucial role in the host's overall health and well-being. [19][20][21] Specifically, studies have extensively explored the regulatory role of gut microbiota in inflammatory bowel disease. [12,22] Observational studies in various countries, including the United States, Europe, Australia, and China, have also shown similar correlations [1,11,22,23] ; however, differences in diet, culture, and lifestyle habits can limit the generalizability of these findings, as the inherent gut microbiota can vary significantly across different countries and cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The human body contains approximately 1 to 2 kg of microorganisms per adult individual, which has been found to play a crucial role in the host's overall health and well-being. [19][20][21] Specifically, studies have extensively explored the regulatory role of gut microbiota in inflammatory bowel disease. [12,22] Observational studies in various countries, including the United States, Europe, Australia, and China, have also shown similar correlations [1,11,22,23] ; however, differences in diet, culture, and lifestyle habits can limit the generalizability of these findings, as the inherent gut microbiota can vary significantly across different countries and cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This is due in part to small sample sizes in clinical trials and heterogeneity in dosing and treatment duration, as well as conditions studied. A recent study of postmenopausal women in China (60% had plasma 25(OH)D levels above 20 ng/mL) found that those with higher vitamin D levels had greater alpha diversity as compared to those with low vitamin D levels (25(OH)D levels <20 ng/mL) (Gong et al, 2022). Higher vitamin D serum and plasma levels have been shown to promote positive, albeit subtle, changes in the gut microbiota in other conditions such as inflammatory bowel disease (e.g., increased microbial diversity, increased butyrate-producing bacteria, and increased serum antimicrobial peptide cathelicidin) (Battistini et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The microorganisms in the gastrointestinal tract are collectively referred to as the gut flora and consist of approximately 10 trillion bacteria ( 84 ). Recent studies have provided substantial evidence for the existence of a “gut microbiota-metabolite-bone axis”, and OP is closely associated with the development and progression of gut microbiota imbalances ( 26 , 27 , 35 , 85 87 ). He et al ( 26 ) combined LC-MS metabolomics with 16S rRNA gene sequencing.…”
Section: Metabolomics In Op Pathogenesis Researchmentioning
confidence: 99%